2016
DOI: 10.1021/acs.chemrestox.6b00323
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Mutagenicity of O-Linked and C-Linked Guanine DNA Adducts: A Combined Experimental and Computational Approach

Abstract: The formation of DNA adducts by the attack of intermediates derived from toxic substances at C8 of 2'-deoxyguanosine (dG) is a common damaging event. Although the majority of studies on C8-dG adducts have focused on lesions containing a C8-N-C tether between the bulky moiety and the nucleobase, the formation of O-linked lesions with a similar tether topology and C-linked adducts involving direct C8-C connectivity have also been uncovered. Several studies have been done to try to better understand the structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…Computational approach. In addition to experimental techniques, computational approaches have been used to study conformational preference of the adducts in DNA, their potential to cause mismatch and mutations, and their interactions with DNA polymerases and repair enzymes [135,136,137]. For example, a multiscale computational approach demonstrated that both O 6 -POB-G and O 6 -PHB-G pair with C and T, with the latter being more mutagenic because of the difference in the bulky moiety hydrogen-bonding pattern [135].…”
Section: Perspectivesmentioning
confidence: 99%
“…Computational approach. In addition to experimental techniques, computational approaches have been used to study conformational preference of the adducts in DNA, their potential to cause mismatch and mutations, and their interactions with DNA polymerases and repair enzymes [135,136,137]. For example, a multiscale computational approach demonstrated that both O 6 -POB-G and O 6 -PHB-G pair with C and T, with the latter being more mutagenic because of the difference in the bulky moiety hydrogen-bonding pattern [135].…”
Section: Perspectivesmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations on damaged DNA is a useful approach for gaining structural insights into the role of adduct formation in the associated mutagenicity. Specifically, MD simulations permit the study of DNA structural dynamics, which can be further used to explain experimental observations. Therefore, as a first step toward understanding the impact of OTA exposure on DNA structure, we previously employed MD simulations to characterize the conformational preferences of DNA containing the OT-G adduct. , The adduct was paired against complementary cytosine in a DNA oligomer containing the Nar I recognition sequence (5′-G 1 G 2 CG 3 CC), which is the known hotspot for mutations induced by other carcinogenic C 8 -G adducts . Our analysis revealed that OTA-damaged DNA likely adopts a mixture of three distinct (i.e., the major groove (B), wedge (W), and base-displaced intercalated (S)) conformations (Figure B–D) regardless of the adduct ionization state and the lesion-site sequence context.…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, in vitro studies on animal tissues treated with OTA used 32 P–postlabeling of the DNA nucleotides to provide evidence for the formation of bulky OTA–DNA adducts, specifically with 2′-deoxyguanosine monophosphate. Further spectroscopic studies characterized three distinct OTA-dG covalent adducts, namely C-linked C 8 –OT-dG, O-linked C 8 –OTA-dG, and N,N-linked N1,N2-OTHQ-dG . Among these lesions, the OT-dG adduct (Figure a) was found to be the most prevalent. , More recent studies have focused on understanding the mutagenicity associated with OTA. For example, an in vitro study on the Sup F gene of the mutation reporter plasmid PS189 in human Ad293 cells and the red / gam gene (Spi – ) at the renal outer medulla of rodents revealed increased mutation frequencies upon OTA exposure.…”
Section: Introductionmentioning
confidence: 99%
“…22 Among these lesions, the OT-dG adduct (Figure 1a) was found to be the most prevalent. 23,24 More recent studies have focused on understanding the mutagenicity associated with OTA. For example, an in vitro study on the SupF gene of the mutation reporter plasmid PS189 in human Ad293 cells 25 and the red/gam gene (Spi − ) at the renal outer medulla of rodents 15 revealed increased mutation frequencies upon OTA exposure.…”
Section: ■ Introductionmentioning
confidence: 99%